Małżeństwo oraz jego cele w opinii zachodnich Ojców Kościoła - Delimata, Małgorzata (Poznańskie Studia Teologiczne, 2008)
The author describes the opinions of the Church Fathers on marriage and its purposes. The question is did some of the Church Fathers condemn matrimony. The answer is no. Some of the Church Fathers emphasized the disadvantages of the matrimony which was seen as an opposite site to the virginity or widows’ state. Moreover, these negative definitions was sometimes connected with the philosophical opinions oh the Church Fathers. Negative or positive image of marriage was also a consequence of the rhetoric utterances. The Church Fathers also emphasized the equal state of husband and wife and family life.